How Asymmetries Between Arctic and Antarctic Climate Sensitivity Are Modified by the Ocean. Issue 23 (12th December 2018) - Singh, H. A.; Garuba, O. A.; Rasch, P. J.
Abstract: We investigate how the ocean response to CO2 forcing affects hemispheric asymmetries in polar climate sensitivity. Intermodel comparison of Phase 5 of the Coupled Model Intercomparison Project CO2 quadrupling experiments shows that even in models where hemispheric ocean heat uptake differences are small, Arctic warming still exceeds Antarctic warming. The polar climate impact of this evolving ocean response to CO2 forcing is then isolated using slab ocean experiments in a state‐of‐the‐art climate model. Overall, feedbacks over the Southern Hemisphere more effectively dissipate top‐of‐atmosphere anomalies than those over the Northern Hemisphere. Furthermore, a poleward shift in ocean heat convergence in both hemispheres amplifies destabilizing ice albedo and lapse rate feedbacks over the Arctic much more so than over the Antarctic. These results suggest that the Arctic is intrinsically more sensitive to both CO2 and oceanic forcings than the Antarctic and that ocean‐driven climate sensitivity asymmetry arises from feedback destabilization over the Arctic rather than feedback stabilization over the Antarctic. Plain Language Summary: Anthropogenic greenhouse gas emissions impact climate globally, but nowhere more so than over the Arctic, a phenomenon known as polar amplification . Surprisingly, the climate response over the Antarctic is much more muted than the climate response over the Arctic, which has been attributed to the large uptake of heat over the Southern Ocean which cools the Southern Hemisphere. Here we show that a weaker climate response over the Antarctic is due, in part, to weaker intrinsic sensitivity to both greenhouse gas forcing and the state of the ocean. Even climate models with similar amounts of heat uptake into the deep ocean in both hemispheres warm more over the Arctic than the Antarctic. Furthermore, similar increases in winter season heat transport into the polar oceans in both hemispheres trigger more destabilizing climate feedbacks over the Arctic than the Antarctic. Therefore, greater climate change over the Arctic than the Antarctic can be expected even if ocean heat uptake or ocean heat transport changes are similar in both hemispheres. Key Points: The Arctic has greater intrinsic sensitivity to ocean state changes than the Antarctic The ocean response triggers more destabilizing radiative feedbacks over the Arctic than the Antarctic Polar radiative feedbacks respond more to increased high‐latitude ocean heat convergence than to subpolar ocean heat uptake